Soil-Transmitted Helminths and Associated Factors among Pre-School Children in Butajira Town, South-Central Ethiopia: A Community-Based Cross-Sectional Study - Shumbej, Teha (PLoS One, 2015)
BACKGROUND: Soil-transmitted helminths (STH) remain a major public health problem, particularly in tropical and sub-tropical regions of the world. Though infections are prevalent among all age groups, the world health organization (WHO) considers Pre-school age children (PSAC), school-aged children, and pregnant women as segments of population at high risk of STH morbidities. OBJECTIVE: This study aimed at determining the prevalence and infection intensity of STH and associated factors among PSAC in Butajira Town, south-central Ethiopia. METHODS: A community-based cross-sectional study was conducted from May to June, 2014 in Butajira Town. The PSAC were selected by systematic sampling technique and invited to participate in the present study. McMaster technique was employed for parasitological analysis of stool samples. Pearson’s Chi-square and Fisher’s exact tests were performed where appropriate to identify any association between STH infection and independent factors. Multivariate logistic regression model was fitted to identify independent predictors of STH among the PSAC. P-value less than 0.05 was considered statistically significant. RESULTS: A total of 377 (with 96% compliance rate) PSAC were able to provide complete data (socio-demographic information and stool sample). The study showed that 23.3% (88/377) PSAC were infected with one or more species of STH. Ascaris lumbricoides was the most prevalent STH (14.9%) followed by Trichuris trichiura (6.4%). The overall infection intensity, expressed as geometric mean for A. lumbricoides, T. trichiura, and hookworms were 229, 178, and 154 eggs per gram of stool, respectively. The multivariate logistic regression model estimated that being in the age group of 36–47 months (AOR: 2.5, 95% CI: 1.2–5.3, P = 0.016), untrimmed finger nail (AOR: 3.2, 95% CI: 1.8–5.5, P < 0.001), and not washing hands before a meal (AOR: 3.0, 95% CI: 1.7–5.4, P < 0.001) were independent predictors of STH infections among the children. CONCLUSION: The present study showed that STH was a public health problem among PSAC in the study area necessitating annual deworming to control morbidities associated with STH. Besides, the existing health education program should also be strengthened to prevent re-infection.